Scoping review of initiation criteria for inhaled nitric oxide in preterm infants (born - Hidehiko Nakanishi; Shin Kato; Erika Ota; Toshinori Nakashima; Katsuya Hirata; Sota Iwatani; Seiji Yoshimoto; Masayuki Ochiai; Daichi Suzuki; Fumihiko Namba; Yohei Minamitani; Miku Hosokawa; et al. (BMJ Open)
Objectives Inhaled nitric oxide (iNO) is a known treatment for pulmonary hypertension (PH) associated with bronchopulmonary dysplasia in preterm infants after 7 days of age (postacute phase). However, a consensus regarding the optimal criteria for initiating iNO therapy in this population in the postacute phase is currently lacking. This study, therefore, aimed to identify the criteria for initiating iNO therapy, alongside the associated clinical and echocardiographic findings, in this population.Design We performed a scoping review using the population-concept-context framework following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.Data sources PubMed, Embase and the Japanese database ‘Ichushi’ were systematically searched for relevant articles published between January 2003 and August 2023.Eligibility criteria This study included randomised controlled trials, prospective and retrospective cohort studies, case–control studies and case series on iNO therapy in the postacute phase for preterm infants born before 34 gestational weeks, written in English or Japanese.Data extraction and synthesis Data screening, extraction and charting were performed independently, with the characteristics and findings of the included studies subsequently summarised.Results We included 10 reports that analysed the data from 10 separate studies. The use of iNO therapy was categorised as prophylactic and rescue purposes. While randomised controlled trials (RCTs) and retrospective analyses indicated the safety of iNO during the postacute phase, the latter highlighted poor prognoses associated with severe cases requiring rescue iNO therapy. Additionally, although echocardiography is currently the primary diagnostic tool for identifying PH in preterm infants, standardised diagnostic criteria are lacking. Further, reports of complications and side effects associated with iNO are rare.Conclusion Our exploration of the initiation criteria for iNO revealed that definitive guidelines have not been established. Nonetheless, iNO administration during the postacute phase appeared to be safe and devoid of complications.Trial registration number UMIN000051498.